Are Students of Isra University Sleep Deprived; A Prospective Study (Medical Forum Monthly, 2024)
Objectives: To assess the sleep pattern of students of Isra University using Pittsburgh sleep quality index &Epworth sleepiness scale. Study Design: Descriptive study. Place and Duration of Study: This study was conducted at Isra University medical college Hyderabad Sind from Jan 2010 to June 2010. Materials and Methods: One hundred medical students of various batches of Isra University were randomly selected for this study. There were 57 females & 43 males. All were given instructions to fill the questionnaires of Pittsburgh sleep quality index &Epworth sleepiness scale. These were then collected and analyzed. Results: Among the students mean Epworth score was 8.37 + .342 and the mean Pittsburgh score was 5.99 + 0.322. Pittsburgh score was above the reference value. There was no difference in these scores between male & female students. In 34% students, Epworth score was above 9 and in 55% students Pittsburgh score was above 5. Both scores were higher in more female students than males. 26% students had less duration of sleep & 13% had difficulty in daily routine due to insufficient sleep. Conclusion: It is concluded that Sleep as assessed by using Epworth sleepiness scale was within normal range. Mean Pittsburgh sleep quality index was above normal range indicating poor sleep quality. Duration of sleep was mainly affected